Cirrhosis: Diagnostic Approach and Complications - Hani Almoallim (Association of American Medical Colleges, 2006)
Abstract This resource is a study guide designed for fourth-year medical students aimed to help them learn the diagnostic approach to cirrhosis and to understand the different complications of cirrhosis. Our system is traditional in that it is lecture-based and teacher-centered. The lectures are usually presented in a passive way to students as they are not used to active learning. This study guide aims to develop active-learning skills in medical students with their first encounter with clinical training. Students are expected to read and work through this guide prior to their attendance to the specified time for the lecture. A whole group discussion is conducted with the entire class that covers the issues raised in this guide. The role of the moderator is to control discussions among students and to assure, with the students, that the objectives of the lecture have been achieved. This is a new method of delivering lectures in a traditional curriculum with multiple engagement strategies. This method could be applied as well to deliver lectures in integrated or problem-based learning curricula. We found it a highly motivating factor for our students to educate themselves. It is extremely important to start the lecture by building on previously learned basic science knowledge. The teacher or a volunteer student may use the board to draw an explanatory diagram.